PENGARUH KARAKTERISTIK GENDER DAN GAYA KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU - Wulan Roudhotul Nasikhah; Sunarni Sunarni; Imam Gunawan; Wulan Roudhotul Nasikhah; Sunarni Sunarni (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
Abstract: This study aims to determine the effect of gender characteristics and leadership style of school principals on teacher performance in State Junior High Schools in Sidoarjo Regency. This study used a quantitative approach with a correlational research design. The results showed that: (1) the gender characteristics of the male principal were gender characteristics with the androgynous type which was a combination of masculine and feminine gender characteristics; (2) the leadership style adopted by the principal is a democratic leadership style that always involves subordinates in the decision-making process; (3) the level of performance of the teachers of Junior High Schools in Sidoarjo Regency is classified as very high, the teacher is able to prepare lesson plans, implement learning, evaluate learning processes and outcomes, and carry out follow-up learning programs very well; (4) partially there is a significant influence between the gender characteristics of the principal's leadership on teacher performance and there is a significant influence between the leadership style of the principal on teacher performance; and (5) simultaneously there is an influence of gender characteristics and leadership style of school principals on teacher performance of State Junior High Schools in Sidoarjo Regency